Identical Word Meaning “Interpretation and Translation” In the Context of Corpus-Based Sentences - Mega Febriani Sya; Ninuk Lustyantie; Miftahulkhairah Anwar (Indonesian Journal of Social Research (IJSR), 2020)
For students whose first language is not a native English speaker, at first glance they will interpret the words "translation" and "interpretation" with the same meaning. Both are indeed similar and both function to transfer one language to another. This study aims to identify the frequency of occurrence of the words "translation" and "interpretation" in several situations in different speech contexts. The method used in this study is the corpus method, to see a large set of authentic data which provides clearer information about the frequency of occurrence of the words "translation" and "interpretation" in several actual contexts of different speech acts. The data collection procedure on the corpus and its analysis uses the facilities provided by the corpus page, namely "chart". The results show that the comparison of the frequency of occurrence of the words "translation" and "interpretation" in the context of different speech shows a significant difference, the word interpretation has a higher occurrence rate of 4282 times than translation, which appeared 1405 times. The meaning of this finding is that the word interpretation is more widely used in the context of formal academic sentences because interpretation does not only have a meaning for itself but can also function as a continuation of meaning from the translation.